Mutual regulation of lactate dehydrogenase and redox robustness - Lin, Yijun; Wang, Yan; Li, Pei-feng (Frontiers in Physiology, 2022)
The nature of redox is electron transfer, by this way energy metabolism brings redox stress. Lactate production is associated with NAD regeneration, which is now recognized to play roles in maintaining redox homeostasis. The cellular lactate/pyruvate ratio could be described as a proxy for the cytosolic NADH/NAD ratio, meaning lactate metabolism is the key of redox regulation. Here we review the role of lactate dehydrogenases in cellular redox regulation, which play as the direct regulator of lactate-pyruvate transforming. Lactate dehydrogenases (LDH) are found in almost all animal tissues, while LDHA catalyzed pyruvate to lactate but LDHB reversed. LDH enzyme activity affects cell oxidative stress with NAD/NADH regulation, especially LDHA recently is also thought as a ROS sensor. We focus on the mutual regulation of LDHA and redox robustness. ROS accumulation regulates the transcription of LDHA, conversely diverse post-translational modifications of LDHA, such as phosphorylation and ubiquitination, play important roles in enzyme activity on ROS elimination, emphasizing the potential role of ROS sensor and regulator of LDHA.